2019
DOI: 10.1186/s12860-019-0213-4
|View full text |Cite
|
Sign up to set email alerts
|

CD40/anti-CD40 antibody complexes which illustrate agonist and antagonist structural switches

Abstract: Background CD40 is a 48 kDa type I transmembrane protein that is constitutively expressed on hematopoietic cells such as dendritic cells, macrophages, and B cells. Engagement of CD40 by CD40L expressed on T cells results in the production of proinflammatory cytokines, induces T helper cell function, and promotes macrophage activation. The involvement of CD40 in chronic immune activation has resulted in CD40 being proposed as a therapeutic target for a range of chronic inflammatory diseases. CD40 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…This epitope partially overlaps the CD40L binding site, but, is distinct from the binding sites of previously reported agonistic mAbs [39,42,43]. Furthermore, studies suggest that binding of this part of CD40 molecule may stabilize CD40 in an "inactive antiparallel state" and prevent downstream signaling [44].…”
Section: Discussionmentioning
confidence: 69%
“…This epitope partially overlaps the CD40L binding site, but, is distinct from the binding sites of previously reported agonistic mAbs [39,42,43]. Furthermore, studies suggest that binding of this part of CD40 molecule may stabilize CD40 in an "inactive antiparallel state" and prevent downstream signaling [44].…”
Section: Discussionmentioning
confidence: 69%
“…The data supports a mechanism where the best antagonist binds to the antiparallel dimer form of the receptor locking in the quiescent state [14,38]. In another example, an antagonist antibody to CD40 (TNFRSF5) has also been shown to bind to the antiparallel dimer form of the receptor [41]. The antibody bound as a single Fab domain making interactions to both CD40 monomers in the dimer.…”
Section: Tnfrsf Antiparallel Dimer Stabilization By Antibodies Effectmentioning
confidence: 53%
“…The antibody bound as a single Fab domain making interactions to both CD40 monomers in the dimer. It was further found that the antiparallel dimer stabilization was essential for antagonism as demonstrated by a closely related antibody that only interacted with a single CD40 monomer and had agonistic activity [41]. As we discuss next, the structure of the herpes virus entry mediator (HVEM) in complex with B and T lymphocyte attenuator (BTLA) represents another example of an antiparallel arrangement with BTLA assisting HVEM oligomerization, and playing a regulatory role in HVEM function.…”
Section: Tnfrsf Antiparallel Dimer Stabilization By Antibodies Effectmentioning
confidence: 95%
“…The importance of the IgG2 hinge on function has been recently confirmed by a study of the anti‐CD40 antibody agonist for cancer immunotherapy 20,22,24 . The structurally rigid IgG2 isoforms with the C127S mutation optimized agonism.…”
Section: Resultsmentioning
confidence: 88%
“…For years, the important antibody region for target specificity was the variable region, but here the focus is on antibody isotypes and isoforms. Antibody isotypes are known to have an impact on function 20–23 . Antibody shuffling between isoforms is defined as the process of creating variants through covalent intrachain interactions in the hinge made naturally in vivo and influenced by manufacturing conditions 22–29 .…”
Section: Resultsmentioning
confidence: 99%